2015
DOI: 10.1186/s12957-015-0444-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in patients with locally advanced gastric cancer treated with S-1 and oxaliplatin as neoadjuvant chemotherapy

Abstract: BackgroundWe wished to evaluate the impact of S-1 combined with oxaliplatin (SOX regimen) as neoadjuvant chemotherapy on surgical outcomes after gastrectomy with D2 lymphadenectomy.MethodsFrom February 2012 to September 2013, 170 patients with American Joint Committee on Cancer (AJCC) stage II–III gastric cancer were assessed retrospectively. Eighty patients underwent neoadjuvant chemotherapy before radical gastrectomy, and 90 patients received surgical treatment with adjuvant chemotherapy. Patients received S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 36 publications
0
33
0
2
Order By: Relevance
“…The pathologic CR rate was 13.8%, which is higher than the 8% and 8.5% observed in another Chinese trial and a Japanese trial with neoadjuvant SOX [32,33], and similar to the 11% observed in the ST03 trial with epirubicin, cisplatin, capecitabine and bevacizumab [34], the 16% observed in the FLOT-4 trial with current standard therapy of docetaxel, oxaliplatin, leucovorin and fluorouracil [35] and the 13.9% observed in a phase II Chinese trial with preoperative chemoradiation and neoadjuvant SOX [36]. The relatively high preoperative ORR of 79.3% was higher than previous reports [7,33,34,36]. The median tumour shrinkage was 89.7%, also higher than expectation.…”
Section: Variablementioning
confidence: 62%
See 1 more Smart Citation
“…The pathologic CR rate was 13.8%, which is higher than the 8% and 8.5% observed in another Chinese trial and a Japanese trial with neoadjuvant SOX [32,33], and similar to the 11% observed in the ST03 trial with epirubicin, cisplatin, capecitabine and bevacizumab [34], the 16% observed in the FLOT-4 trial with current standard therapy of docetaxel, oxaliplatin, leucovorin and fluorouracil [35] and the 13.9% observed in a phase II Chinese trial with preoperative chemoradiation and neoadjuvant SOX [36]. The relatively high preoperative ORR of 79.3% was higher than previous reports [7,33,34,36]. The median tumour shrinkage was 89.7%, also higher than expectation.…”
Section: Variablementioning
confidence: 62%
“…Neoadjuvant chemotherapy may offer benefits for these patients. Combination chemotherapy with S-1 plus oxaliplatin (SOX) for advanced gastric cancer has shown promising efficacy with acceptable toxicity [4e6] and was recommended as neoadjuvant chemotherapy for patients with locally advanced gastric cancer [7,8]. Nevertheless, there are still some patients who cannot benefit from the SOX regimen because of the heterogeneity of their gastric carcinoma or the homogenous insensitivity of tumour to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy obviously does not act as a protective agent, but fitter patients more often receive such therapy. Previous observational and randomized studies showed that neoadjuvant chemotherapy does not result in less morbidity or mortality. In the MAGIC trial, no significant difference was seen in rates of postoperative complication (45·7 versus 45·3 per cent) or mortality (5·6 versus 5·9 per cent) between patients who did or did not receive neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 77%
“…Clinically, chemotherapy is often used to treat the metastatic lung cancer in combination with surgery and radiotherapy. 8,9 However, the efficacy of the existing chemotherapeutics for lung cancer is limited by several drawbacks such as insufficient drug concentrations in tumors, drug resistance of tumor cells, and systemic toxicity. Recent attention has been paid to the development of more selective anticancer agents to treat the cancer and to minimize the side effects.…”
Section: Introductionmentioning
confidence: 99%